Mastering the ultimate high ground : next steps in the military uses of space - Lambeth, Benjamin S. (RAND, Project Air Force, 2003)
The author assesses the military space challenges that face the Air Force and the nation in light of the findings and recommendations of the congressionally mandated Space Commission, released in January 2001. After reviewing the main milestones in the Air Force's involvement in space since its creation as an independent service in 1947, he examines the circumstances that occasioned the Space Commission's creation, as well as the conceptual and organizational roadblocks that have impeded a more rapid growth of U.S. military space capability. He concludes that the Air Force faces five basic challenges with respect to space: continuing the operational integration of space with the three terrestrial warfighting mediums while ensuring the organizational differentiation of space from Air Force air; effectively wielding its newly granted military space executive-agent status; realizing a transparent DoD-wide budget category for space; showing progress toward fielding a meaningful space control capability while decoupling that progress from any perceived taint of force-application involvement; and making further progress toward developing and nurturing a cadre of skilled space professionals within the Air Force.